Towards A Pre-Modern Psychiatry - Booth, J. author. aut Link
XV, 221 p.
Keywords: The author applies modified versions of pre-modern philosophy (including Aristotle and Aquinas) to psychiatry, arguing that the work of the Aristotelian philosopher, Christian and former Marxist, Alasdair MacIntyre is ideally placed to bring about a transformation of psychiatry from its current captivity to the modern scientific technical paradigm.